Exploring hot topics and evolutionary paths in the Diagnosis-Related Groups (DRGs) field: a comparative study using LDA modeling - Xinrui Chen; Meng Zhang; Qingqing Bu; Bo Tan; Peng Peng; Yilin Zhou; Yuqin Tang; Xiaoqin Tian; Dan Deng (BMC, 2024)
Abstract Background This study reviews the research status of Diagnosis-related groups (DRGs) payment system in China and globally by analyzing topical issues in this field and exploring the evolutionary trends of DRGs in different developmental stages. Methods Abstracts of relevant literature in the field of DRGs were extracted from the China National Knowledge Infrastructure (CNKI) database and the Web of Science (WoS) core database and used as text data. A probabilistic distribution-based Latent Dirichlet Allocation (LDA) topic model was applied to mine the text topics. Topical issues were determined by topic intensity, and the cosine similarity of the topics in adjacent stages was calculated to analyze the topic evolution trend. Results A total of 6,758 English articles and 3,321 Chinese articles were included. Foreign research on DRGs focuses on grouping optimization, implementation effects, and influencing factors, whereas research topics in China focus on grouping and payment mechanism establishment, medical cost change evaluation, medical quality control, and performance management reform exploration. Conclusions Currently, the field of DRGs in China is developing rapidly and attracting deepening research. However, the implementation depth of research in China remains insufficient compared with the in-depth research conducted abroad.